PENGARUH POLA ASUH ORANG TUA TERHADAP KECERDASAN SOSIAL SISWA KELAS V MADRASAH IBTIDAIYAH NURUL ISLAM CIBINONG DEPOK - Alvi Syahrini; Henri Peranginangin Tanjung; Abdur Rahim (Al-mujahidah, 2023)
Parents are the first people who can be invited to interact, adapt or socialize well to people in their environment. However in the phenomena that there are sometimes found children with poor social intelligence, so often experience social problems in socializing such as difficulty adapting, lack of sense of four with people around and often throwing tantrums with others. One of the factors causing this is due to the lack of good social intelligence of children could be due to the adaption of parenting parents. This is the background of the writer influence of parenting parents on social intelligence of students of the 5th grade MI Nurul Islam Cibinong Depok. The purpose of this study was to determine parenting style of parents, the level of social intelligence of students and the effect of parenting style on social intelligence of fifth grade students at Madrasah Ibtidaiyah Cibinong Depok. The method in this research is Ex-post Facto quantitative. The population and sample were all 20 grade V students at Madrasah Ibtidaiyah Nurul Islam Cibinong Depok. The data collection tool in this study was a questionnaire given to fifth grade students at Madrasah Ibtidaiyah Nurul Islam Cibinong Depok. The questionnaire instrument, which included the parenting style questionnaire given to the social intelligence questionnaire given to fifth grade students at Madrasah Ibtidaiyah Cibinong Depok, had its validity and reliability tested. The results of the research: that the majority of the parents of MI Nurul Islam Cibinong Depok are adopting democratic parenting as many as 11 parents, while parents who apply permassive parenting as much as 4 parents, and parents who apply authoritarian parenting as much as 5 parents. And the level of social intelligence of students namely, 12 students with moderate intelligence, 5 students with low intelligence, and 3 students with high social intelligence. From the result of hypothesis testing, it is known that the simple linear regression value of parenting parents in students’ social intelligence 59, 855 with sig. (2-tailed) of 0, 000. And by comparing the significant leel of 0, 05 (5%) sig, (2-tailed) is smaller than 0, 05 (5%). Which means that Ho is rejected and Ha Fail to be rejected. Which means that there is an influence between parenting on the social intelligence of 5th grade students MI Nurul Islam Cibinong Depok. And from the test of determination (r), it is stated that the influence of parenting parents on students’ social intelligence is 0,769%.